Nondestructive Total Excitation-Emission Fluorescence Microscopy Combined with Multi-Way Chemometric Analysis for Visually Indistinguishable Single Fiber Discrimination - Muñoz De La Peña, Arsenio (2016)
The potential of total excitation-emission fluorescence microscopy combined with multiway chemometric analysis was investigated for the nondestructive forensic analysis of textile fibers. The four pairs of visually indistinguishable fibers consisted of nylon 361 dyed with acid yellow 17 and acid yellow 23, acetate satin 105B dyed with disperse blue 3 and disperse blue 14, polyester 777 dyed with disperse red 1 and disperse red 19, and acrylic 864 dyed with basic green 1 and basic green 4. Excitation emission matrices were recorded with the aid of an inverted microscope and a commercial spectrofluorimeter. The full information content of excitation-emission matrices was processed with the aid of unsupervised parallel factor analysis (PARAFAC), PARAFAC supervised by linear discriminant analysis (LDA), and discriminant unfolded partial least-squares (DU-PLS). The ability of the latter algorithm to classify the four pairs of fibers demonstrates the advantage of using the multidimensionality of fluorescence data formats for the nondestructive analysis of forensic fiber evidence.